2011
DOI: 10.1002/jat.1762
|View full text |Cite
|
Sign up to set email alerts
|

Role of glial cells in manganese neurotoxicity

Abstract: The objectives of this focused review are to (i) provide a systematic overview of recent advances pertaining to the role of glia, namely microglia and astrocytes, in the neuropathology associated with excessive exposure to manganese (Mn), (ii) highlight possible mechanisms and factors involved in Mn-modulated, glia-derived neuroinflammation, and (iii) discuss the implications of excessive neuroinflammation on neuronal injury within the context of Mn overexposure. As this is not meant to be a comprehensive revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 102 publications
3
47
0
Order By: Relevance
“…26,27) Mn can induce neuronal damage directly and also indirectly enhance neuronal cell death through activation of microglia. 28) Microglia easily respond to Mn and release ROS and inflammatory mediators, such as proinflammatory cytokines, nitric oxide (NO), and prostaglandins, inducing detrimental toxicity to neighboring neurons. 27) Although there are limited reports on the effects of Mninduced toxicity on glial cells, some studies suggested that self-produced ROS can stimulate degradation of ferritin in microglia and subsequent microglial cell death.…”
Section: Discussionmentioning
confidence: 99%
“…26,27) Mn can induce neuronal damage directly and also indirectly enhance neuronal cell death through activation of microglia. 28) Microglia easily respond to Mn and release ROS and inflammatory mediators, such as proinflammatory cytokines, nitric oxide (NO), and prostaglandins, inducing detrimental toxicity to neighboring neurons. 27) Although there are limited reports on the effects of Mninduced toxicity on glial cells, some studies suggested that self-produced ROS can stimulate degradation of ferritin in microglia and subsequent microglial cell death.…”
Section: Discussionmentioning
confidence: 99%
“…65 Moreover, Mn potentiates the release of several inflammatory molecules such as prostaglandins, cytokines including TNF-a, Interleukin (IL)-6, and IL-1b, and nitric oxide from the activated glial cells. [66][67][68][69] Among these inflammatory cytokines, TNF-a and IL-1b have been shown to decrease GLT-1 mRNA and protein expression levels in astrocytes, acting as negative regulators of GLT-1. 70,71 Mn induces nitric oxide synthase 2 (NOS2, an inflammatory gene) via NFkB activation in astrocytes.…”
Section: Apoptosis and Inflammationmentioning
confidence: 99%
“…High doses of Mn have been shown to induce production of the cytokines TNF-alpha, IL1-beta, and IL-6 and the production of hydrogen peroxide 98,99 . Mn also increased the production of both cytokines and free radicals when cells were simultaneously stimulated with LPS.…”
Section: Microglial Activation and Inflammationmentioning
confidence: 99%
“…Mn also increased the production of both cytokines and free radicals when cells were simultaneously stimulated with LPS. The production of cytokines proceeds through the activation of the neuroinflammatory NFkappa-B and the MAP kinase p38 [98][99][100] . The release of both cytokines and free radical reactive oxygen and nitrogen species from Mn activated microglia can exert deleterious effects on neighboring neurons.…”
Section: Microglial Activation and Inflammationmentioning
confidence: 99%